2016
DOI: 10.1038/srep22847
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming doxorubicin resistance of cancer cells by Cas9-mediated gene disruption

Abstract: In this study, Cas9 system was employed to down-regulate mdr1 gene for overcoming multidrug resistance of cancer cells. Disruption of the MDR1 gene was achieved by delivery of the Cas9-sgRNA plasmid or the Cas9-sgRNA ribonucleoprotein complex using a conventional gene transfection agent and protein transduction domain (PTD). Doxorubicin showed considerable cytotoxicity to the drugresistant breast cancer cells pre-treated with the RNA-guided endonuclease (RGEN) systems, whereas virtually non-toxic to the untrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 29 publications
0
44
0
Order By: Relevance
“…MCF‐7/ADR cells were treated with doxorubicin after disruption of MDR1 by Cas9‐sgRNA, and possible drug sensitivity recovery was examined. The potency of doxorubicin was enhanced in the cells treated with CRISPR/Cas9 expression construction using a proper delivery platform 80. This result indicates that disruption of this drug resistance‐related gene can be considered to overcome MDR in cancer cells.…”
Section: How Crispr/cas9 Overcomes Drug Resistancementioning
confidence: 91%
See 1 more Smart Citation
“…MCF‐7/ADR cells were treated with doxorubicin after disruption of MDR1 by Cas9‐sgRNA, and possible drug sensitivity recovery was examined. The potency of doxorubicin was enhanced in the cells treated with CRISPR/Cas9 expression construction using a proper delivery platform 80. This result indicates that disruption of this drug resistance‐related gene can be considered to overcome MDR in cancer cells.…”
Section: How Crispr/cas9 Overcomes Drug Resistancementioning
confidence: 91%
“…Based on the strategy described by Ha et al,80 after identification of the specific expression of genes related to drug resistance mentioned above, they could be edited by the CRISPR/Cas9 system to recover drug sensitivity, which makes downregulation of efflux‐mediated chemotherapy resistance available. This is a promising way to overcome MDR of cancer cells.…”
Section: How Crispr/cas9 Overcomes Drug Resistancementioning
confidence: 99%
“…Five additional articles published between 2016 and 2018 applied a similar approach to knockout ABCB1/MDR1in various cell lines. These investigated if the knockout of ABCB1 could reverse resistance in human cancer derived cell lines (Ha et al, 2016;Liu et al, 2016;Yang et al, 2016b;Takahashi et al, 2017;Norouzi-Barough et al, 2018). As expected, these studies showed decreased ABCB1/MDR1 mRNA or protein expression levels and increased intracellular accumulation, or increased sensitivity in the MDR1 knockout cells using MDR1 substrates such as rhodamine 123, doxorubicin, and/or carfilzomib.…”
Section: Drug Transportersmentioning
confidence: 99%
“…This approach has already been applied in EFGR mutant lung cancer and osteosarcomas, though not in TNBC . CRISPR/Cas9 was engineered with a gRNA to target the md1 gene that codes for a drug efflux pump responsible for a prominent mechanism in cells that become drug resistant . Three Cas9/gRNA delivery methods were explored (Cas9/gRNA plasmid delivered by the protein transduction domain TAT, Cas9 Protein/gRNA complex delivered by Lipofectamine, and Cas9/gRNA complex delivered by cell penetration peptide) and yielded similar gene and protein disruption between 50–60% in MCF7 breast cancer cells.…”
Section: Crispr Technology For Breast Cancer Therapymentioning
confidence: 99%